Congenital Nasolacrimal Duct Obstruction: Presentation and Mangement - Sanaullah Jan, Shad Mohammad, Nazullah Khan, Mohammad Naeem Khan (Pakistan Journal of Ophthalmology, 2006)
Purpose: To study presentation of congenital nasolacrimal duct obstruction and its outcome after conservative treatment and probing. Material and Methods: 100 eyes of 81 children were studied. Children were divided into two groups. In group 1, children upto age of 6 months were included. They were initially treated conservatively with massage and topical antibiotics. In 2nd group children between age 6 months to 3 years were included. They all had conservative treatment but had not responded to it. So they underwent probing. Results: In first group, out of 25 patients with 30 involved eyes, 83% were relieved of symptoms with conservative treatment. In 2nd group, out of 56 children with 70 involved eyes, 87% responded to 1st probing, 9% responded to 2nd probing while 4% were not relieved even with 3rd probing. The overall success in both conservative treatment and probing was 97%. Conclusion: Most of the children with congenital nasolacrimal duct obstruction are relieved with conservative treatment. In the remaining unsuccessful cases probing is done, which is successful in majority of children.